Handbook of research on mobile multimedia - Ibrahim, Ismail Khalil; Gale Group (Hershey, Penn. Idea Group Reference, 2006)
"This handbook provides insight into the field of mobile multimedia and associated applications and services"--Provided by publisher.
Foreword -- Preface -- Section I: Basic concepts -- Section II: Standards and protocols -- Section III: Multimedia information -- Section IV: Applications and services -- About the authors -- Index.
Electronic reproduction.
Keywords: Mobile communication systems; Wireless communication systems; Multimedia systems; Mobile computing; Electronic books